2019
DOI: 10.1002/jeab.513
|View full text |Cite
|
Sign up to set email alerts
|

The effect of reinforcement probability on time discrimination in the midsession reversal task

Abstract: We examined how biasing time perception affects choice in a midsession reversal task. Given a simultaneous discrimination between stimuli S1 and S2, with choices of S1 reinforced during the first, but not the second half of the trials, and choices of S2 reinforced during the second, but not the first half of the trials, pigeons show anticipation errors (premature choices of S2) and perseveration errors (belated choices of S1). This suggests that choice depends on timing processes, on predicting when the contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
31
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(53 citation statements)
references
References 31 publications
20
31
2
Order By: Relevance
“…5 for examples). These performance idiosyncrasies are consistent with previous reports (Rayburn-Reeves and Cook, 2016;Santos et al, 2019) and might require further research.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…5 for examples). These performance idiosyncrasies are consistent with previous reports (Rayburn-Reeves and Cook, 2016;Santos et al, 2019) and might require further research.…”
Section: Discussionsupporting
confidence: 91%
“…Whence the asymmetry? The results from this and similar studies (McMillan & Roberts, 2012; Santos et al, 2019; Smith et al, 2017, Zentall et al, 2019) indicate that pigeons' performance in the MSR task is not exclusively controlled by timing. Local cues, including the response outcome of previous trials, may also influence choice on the next trial.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…But as we have shown (Rayburn-Reeves, Molet, & Zentall, 2011), pigeons respond to the feedback from an unpredictable reversal much more slowly when it occurs early in the session than when it occurs later in the session. Carvalho et al (2019) question my interpretation of why reducing the probability of reinforcement for correct S2 responses (from 100% to 20%) reduces errors (especially anticipatory errors) but reducing the probability of reinforcement for correct S1 responses (from 100% to 20%) actually increases errors (especially anticipatory errors; Santos, Soares, Vasconcelos, & Machado, 2019). In my target article, I suggested that reducing the probability of reinforcement for correct S2 responses from 100% to 20% reduces the response competition between S1 and S2 and encourages the pigeons to choose based on the consequences of choice of S1 alone.…”
Section: The Midsession Reversal Taskmentioning
confidence: 98%